Motherland Lyrics in the Literature of Artai, the Famous Poet of Inner Mongolia - Burentugs, Togtomj (Mongolian Language and Literature Studies, 2025)
In Artai’s poem on the theme of the motherland, there is a lot of nostalgia for the country. There are many poems where he also wrote with treasure about the earth and stones of his beloved, proud and admired homeland. He has surprisingly well described the precise connection of time in poetry on motherland role narrating that motherland supports you from when you start to walk until you aspire to horses and one leans on it when he feels weak. It can be said that his poems on the theme of the motherland are simple in terms of imagery and composition vocabulary and when he embosses something he is excellent at expressing its essence without losing it. It is obvious that he has embedded his detailed description in his poems on the theme of the motherland and that he has touched the hearts of others and received the love and respect of his people with his ordinary language. Even though these poems on the theme of the motherland of Artai’s poems have a lot of simple language the meaning behind them is deeply reflected with the narrative closely connected to the cause and reason the great worship of non-lyrical understanding and the love and pride for the motherland. For this reason, it can conclude that in addition to these poems, many of his poems in praise of the motherland are popular among the Mongolian people in China. Өвөр монголын нэрт яруу найрагч Артайн эх орны сэдэвт бүтээлийн онцлог Хураангуй: Эх орны тухай магтан шүлэглэсэн бүтээл хэн бүхний зүрх сэтгэлд гүн хоногшдог. Учир нь хүн бүрд эгнэгт хайрлаж явах сэтгэлийн хэмжүүр гэж бий. Артайн эх орны шүлгүүдэд нутгаа санасан сэтгэл багагүй илэрдэг. Мөн нутгийнхаа ширхэг шороо, чулуу бүхнийг хайрлаж, бахархаж, биширч, нандигнаж бичсэнээрээ ялгарч байна. Ялангуяа тэнтэр тунтар алхахаас эхлэн тэмүүлэх хүлгийн зоон дээр гарсан, улмаар тэнхээ муудаад өтлөхийн цагт түшээд авна хэмээн цаг хугацааны нарийн уялдаа холбоог шүлэглэсэн нь бий. Түүний бичсэн эх орны сэдэвт шүлгүүд хэл найруулга, үгийн сангийн хувьд эгэл энгийн ч ямар нэгэн зүйлийг товойлгон цэцлэхдээ түүнийхээ мөн чанарыг алдагдуулалгүй илэрхийлдгээрээ гарамгай нь дүрслэлийн уран чадвартай нь холбогдоно. Уран чамин, нарийн нандин дүрслэлээ эх орны сэдэвт шүлэгтээ илүүтэй шигтгэдэг нь Артайн туурвил зүйн мөн чанарыг тодорхойлохын зэрэгцээ уншигчдын зүрх сэтгэл, хайр хүндэтгэлийг хүлээхэд онцгой байртай байна. Түлхүүр үгс: Артай, эх орон, яруу найраг, утга уянга, онцлог